2020
DOI: 10.1021/acs.cgd.9b01565
|View full text |Cite
|
Sign up to set email alerts
|

New Theoretical Insight into Fluorination and Fluorine–Fluorine Interactions as a Driving Force in Crystal Structures

Abstract: Fluorination of compounds causes an increase in the proton-donating ability and a decrease in the proton-accepting capacity of groups in their vicinity. The formation of F···F interactions is followed by the shift of the electron density in the area of F···F contact, which creates a new region with a larger surface area, a higher negative potential, and, hence, a more pronounced accepting ability. The new region also has a greater ability to form multiple (simultaneous) interactions with species from the envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 49 publications
5
31
0
Order By: Relevance
“…On the other hand, there is evidence for the existence of attractive interactions between fluorine atoms. 56–58 Halogen bonding interactions are characterized by the X 1 ⋯X 2 distance and two angles θ 1 = C–X 1 ⋯X 2 and θ 2 = X 1 ⋯X 2 –C and classified into three types: 1) 0° ≤ | θ 1 − θ 2 | ≤ 15° (type I); 2) | θ 1 − θ 2 | ≥ 30° (type II); 3) 15° ≤ | θ 1 − θ 2 | ≤ 30° (quasi-type I/type II). 54,55 The crystal structures of lanthanide CPs with a tetrafluoroterephthalate linker have F⋯F contacts of type I.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there is evidence for the existence of attractive interactions between fluorine atoms. 56–58 Halogen bonding interactions are characterized by the X 1 ⋯X 2 distance and two angles θ 1 = C–X 1 ⋯X 2 and θ 2 = X 1 ⋯X 2 –C and classified into three types: 1) 0° ≤ | θ 1 − θ 2 | ≤ 15° (type I); 2) | θ 1 − θ 2 | ≥ 30° (type II); 3) 15° ≤ | θ 1 − θ 2 | ≤ 30° (quasi-type I/type II). 54,55 The crystal structures of lanthanide CPs with a tetrafluoroterephthalate linker have F⋯F contacts of type I.…”
Section: Resultsmentioning
confidence: 99%
“…Among their finds, it can be highlighted that complexes involving electron-withdrawing substituents obtained more favorable binding energy. This electron-withdrawing substituent character was also explored by Janjić et al [19]. In their study, the replacement of a hydrogen by a fluorine resulted in an increased interaction energy and in the number of multiple interactions of F•••F contacts.…”
Section: Introductionmentioning
confidence: 88%
“…Previous work has demonstrated that dominant partial charge concentration, either positive or negative, on specific parts of interacting molecules have important influence in the intermolecular interaction [44][45][46]. Due its high electronegativity, fluorine has the capacity of electron-withdrawing from neighbor atoms [19,47,48] and, for this reason, this atom has become an interesting substituent in many chemical systems in the search for changes the electronic properties or to enhance intermolecular interaction [47,49].…”
Section: Interaction Energies and Mep Analysis Of Supramolecular Dimers Of 1 Andmentioning
confidence: 99%
See 2 more Smart Citations